Characterization of the wave resource variability in the French Basque coastal area based on a high-resolution hindcast. (November 2021) - Delpey, Matthias; Lastiri, Ximun; Abadie, Stéphane; Roeber, Volker; Maron, Philippe; Liria, Pedro; Mader, Julien
Abstract: A wave resource characterisation is presented for the French Basque coastal region, with a specific focus on Bayonne nearshore area. The study is derived from a 10-year hindcast computation performed with a very high-resolution coastal implementation of a SWAN model. After a detailed validation of the model in intermediate and shallow water, the spatial, temporal, and spectral distributions of the local nearshore wave energy climate are characterized. Refraction over a local submarine canyon splits the coastal domain into two main regions with different general characteristics. In the southern Basque region, the spatial fluctuations of the wave resource increase drastically in shallow water. Variability nearshore was shown to be significantly higher than over the deeper part of the shelf. Noticeable hot-spots are found in the nearshore area around Bayonne, where the local wave resource substantially exceeds the outer shelf incident energy flux. Seasonal to hourly temporal fluctuations are also characterized at different nearshore locations and found to be very pronounced. The major wave resource variations found at reduced space-time scales highlight the strong influence of local small-scale bathymetry features in the Basque nearshore region.